2020
DOI: 10.1109/tro.2020.3006717
|View full text |Cite
|
Sign up to set email alerts
|

CPL-SLAM: Efficient and Certifiably Correct Planar Graph-Based SLAM Using the Complex Number Representation

Abstract: In this paper, we consider the problem of planar graph-based simultaneous localization and mapping (SLAM) that involves both poses of the autonomous agent and positions of observed landmarks. We present CPL-SLAM, an efficient and certifiably correct algorithm to solve planar graph-based SLAM using the complex number representation. We formulate and simplify planar graph-based SLAM as the maximum likelihood estimation (MLE) on the product of unit complex numbers, and relax this nonconvex quadratic complex optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
(180 reference statements)
3
15
0
Order By: Relevance
“…In some modern algorithms for solving pose-graph SLAM such as [21] and planar pose-graph and feature-based SLAM such as [7], the original SLAM problem is first reformulated as a rotation only problem, and then semidefinite relaxation and Riemannian staircase optimisation are applied. Similarly, in the proof of the region of attraction for GN in [5], the posegraph SLAM problem is also transferred into an orientation only problem first to facilitate the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some modern algorithms for solving pose-graph SLAM such as [21] and planar pose-graph and feature-based SLAM such as [7], the original SLAM problem is first reformulated as a rotation only problem, and then semidefinite relaxation and Riemannian staircase optimisation are applied. Similarly, in the proof of the region of attraction for GN in [5], the posegraph SLAM problem is also transferred into an orientation only problem first to facilitate the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[14] [13][2] [12][1] [19]). In particular, some recently developed algorithms can efficiently recover certifiably globally optimal solutions to the SLAM problems under certain conditions using techniques ranging from semidefinite relaxation and Riemannian Staircase procedure [21] [3], sparsebounded sum of squares programming [17], and complex number representation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system can be seen as a spring-mass model [143] and solved by computing the minimal energy state of the model. Some of the popular open source graph-based algorithms are g2o [117], GTSAM [144], HOG-Man [145], KinectFusion [146], PTAM [147], TORO [148], CPL-SLAM [149], [150] etc. A comparative analysis of these three paradigms has been shown in Table 5.…”
Section: X K N and N Number Of Landmarks In The Map As M Kmentioning
confidence: 99%
“…The problem was further studied in [28] where it was shown that for low noise regimes, the SDP relaxation is always tight. In robotics, SDP relaxations for estimating rigid transformations in simultaneous localization and mapping (SLAM) have been explored in a number of recent papers [8,11,12,19,32]. Again, the empirical performance is generally good, the optimal solutions can be efficiently computed [5], and the relaxations are shown to be tight for bounded noise levels.…”
Section: Related Workmentioning
confidence: 99%